Program Pelatihan Penulisan Artikel Ilmiah: Menuju Guru Berkualitas - Nine Febrie Novitasari (Universitas Mathla'ul Anwar Banten, 2019)
PROGRAM OF SCIENTIFIC ARTICLE WRITING TRAINING: TOWARDS QUALIFIED TEACHERS. Writing scientific articles is one of teacher’ efforts to improve their quality and develop their professionalism. Unfortunately, their reading interest and wriitng habit are still low. This makes the teachers have difficulties when they have to submit a promotion because they do not have enough background knowledge and understanding in writing scientific articles, while one of the requirements for submitting a promotion is to publish a scientific article. Therefore, a training on scientific article writing was held for teachers in Situbondo to provide knowledge and skills for them to write scientific articles. After participating in this activity, teachers are expected to be able to publish scientific articles and be able to improve the quality and professionalism of their work so that the quality of education becomes better.